Managers' open innovation and business performance in SMEs: A moderated mediation model of job crafting and gender - Fouzia Hadi Ali; Muhammad Ali; Sania Zahra Malik; Muhammad Ali Hamza; Hafiz Fawad Ali (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
There is growing acceptability in redesigning jobs to achieve goals and objectives nowadays. Employees who indulge in exploiting and exploring opportunities for the business tend to craft their jobs, which can help to enhance business performance. This study aims to examine that how ambidextrous managers in small and medium enterprises (SMEs) craft their tasks as a strategy for open innovation to enhance business performance. This study also attempts to assess the moderating role of gender in evaluating the relationship. Simple random sampling is used to administer a structured questionnaire to 650 operations managers employed in service-sector SMEs. The findings reveal that, when male managers involve in explorative and exploitative activities, they tend to craft their jobs more as compared to females. In turn, when jobs are redesigned, it brings a positive impact on business performance as perceived by the managers. The study provides implications for the policy makers with regard to device measures to enhance the job crafting capacity of managers with specific attention to female managers in the case of small and medium enterprises. The present study provides a novel explanation of the relationship between manager ambidextrous behavior and business performance through the mediation of job crafting among top managers working in small and medium organizations, with an overarching view of gender.
Keywords: 650; open innovation; manager ambidexterity; job crafting; perceived business performance; gender; small and medium enterprises